Chemical composition of manganese nodules from the Mariana basin and the Magellan seamounts - Maruyama, Shuji; Takeda, Hideo (PANGAEA, 2022)
In 1972, the R/V Bosei was commissionned by the Geological Survey of Japan (GSJ) to undertake a survey within the framework of the Basic investigations for development of deep sea mineral resources program. Conducted in November-December 1972 the expedition covered the Mariana basin and the Magellan seamounts. Fifteen bottom samples were collected and ferromanganese nodules were obtained at a depth over 5000 meters. Eleven manganese nodules from the the Mariana basin and the Magellan seamounts have been analysed by the Geological Survey of Japan (GSJ). After drying at 110°C for two or three hours, 0.5 g of the powdered samples were treated by HF and analyzed by atomic absorption spectrophotometry.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment